Strategi Pengembangan Usaha Mikro Kecil Dan Menengah (Studi Kasus Jamu Tradisional Ibu Hadi) - Heru Suheryadi; Nicko Gana Saputra; Siti Sarah Farah Dilla (Politeknik Sahid, 2021)
Jamu is a traditional alternative medicine. In Indonesia, the herbal medicine industry has received government attention by issuing regulations on standardization in the processing of herbal medicine. Ibu Hadi's traditional herbal medicine business industry is one of the Micro, Small and Medium Enterprises (MSME) units that focus on selling traditional herbal medicine. There needs to be special attention to the development system of Micro, Small and Medium Enterprises (MSME). After conducting a research survey, several alternative strategies are needed to find out which alternative strategy is appropriate to use as an effort to develop the herbal medicine industry in Ibu Hadi's Traditional Herbal Medicine business, study internal (IFE) and external (EFE) environmental analysis, external internal matrix (IE), Strengths, Weaknesses, Opportunities, Threats (SWOT) matrices has been done. The Quantitative Strategic Planning Matrix (QSPM), from the analysis results obtained 12 internal factors and 10 external factors. Meanwhile, for alternative strategies, there are 6 alternatives obtained from the SWOT matrix and IE matrix. In the QSPM matrix, strategic priorities are obtained, namely maintaining prices and improving the quality of herbal medicine and maintaining the purity of herbs without medicinal chemicals to increase customer satisfaction, using the latest tools or technology to improve quality and speed up the herbal medicine production process, working with several online transportations applications to facilitate customers. In buying herbal medicine, holding promotions on social media to increase sales and marketing reach, adding or innovating for durable products to be marketed in the market, as well as making product packaging innovations such as the appearance of ready-to-drink herbal bottle, and become more practical.